Do South-South Trade Agreements Increase Trade? : Commodity-Level Evidence from COMESA - Mayda, Anna Maria (IMF Working Papers; Working Paper ;, 2007)
South-South trade agreements are proliferating: Developing countries signed 70 new agreements between 1990 and 2003. Yet the impact of these agreements is largely unknown. This paper focuses on the static effects of South-South preferential trade agreements stemming from changes in trade patterns. Specifically, it estimates the impact of the Common Market for Eastern and Southern Africa (COMESA) on Uganda's imports between 1994 and 2003. Detailed import and tariff data at the 6-digit harmonized system level are used for more than 1,000 commodities. Based on a difference-in-difference estimation strategy, the paper finds that-in contrast to evidence from aggregate statistics-COMESA's preferential tariff liberalization has not considerably increased Uganda's trade with member countries, on average across sectors. The effect, however, is heterogeneous across sectors. Finally, the paper finds no evidence of trade-diversion effects.